Development of a Novel Pre-Vascularized Three-Dimensional Skin Substitute Using Blood Plasma Gel. Issue 10 (October 2018) - Dai, Niann-Tzyy; Huang, Wen-Shyan; Chang, Fang-Wei; Wei, Lin-Gwei; Huang, Tai-Chun; Li, Jhen-Kai; Fu, Keng-Yen; Dai, Lien-Guo; Hsieh, Pai-Shan; Huang, Nien-Chi; Wang, Yi-Wen; Chang, Hsin-I; et al.
Skin substitutes with existing vascularization are in great demand for the repair of full-thickness skin defects. In the present study, we hypothesized that a pre-vascularized skin substitute can potentially promote wound healing. Novel three-dimensional (3D) skin substitutes were prepared by seeding a mixture of human endothelial progenitor cells (EPCs) and fibroblasts into a human plasma/calcium chloride formed gel scaffold, and seeding keratinocytes onto the surface of the plasma gel. The capacity of the EPCs to differentiate into a vascular-like tubular structure was evaluated using immunohistochemistry analysis and WST-8 assay. Experimental studies in mouse full-thickness skin wound models showed that the pre-vascularized gel scaffold significantly accelerated wound healing 7 days after surgery, and resembled normal skin structures after 14 days post-surgery. Histological analysis revealed that pre-vascularized gel scaffolds were well integrated in the host skin, resulting in the vascularization of both the epidermis and dermis in the wound area. Moreover, mechanical strength analysis demonstrated that the healed wound following the implantation of the pre-vascularized gel scaffolds exhibited good tensile strength. Taken together, this novel pre-vascularized human plasma gel scaffold has great potential in skin tissue engineering.